Workplace Social Capital in the Development and Implementation of a Senior Policy - Albertsen, Karen; Jensen, Per H.; Gensby, Ulrik; Pedersen, Flemming (Nordic Journal of Working Life Studies, 2024)
Senior policies have been introduced by many Danish companies with the intention of retaining senior employees, but implementation can be challenging and may create tension at the workplace.This study aims to explore how social capital at the workplace may support or counteract the development and implementation of senior policies. A qualitative case study approach was used to collect and analyze interview data from managers, union- and H&S representatives, and senior employees at eightheen workplaces.The analysis reveals that successful development and implementation of a senior policy rely on legitimacy, transparency, and involvement of relevant parties in the process, as well as a good fit between the policy and the companies’ structure for collaboration. Workplace social capital is discussed as a supporting factor for senior employee retention, and a reciprocal positive relationship between implementing senior policies and procedures and the social capital of the workplace is suggested.